Reservoirs of plant virus disease: Occurrence of wheat dwarf virus and barley/cereal yellow dwarf viruses in Sweden - Yazdkhasti, Elham; Hopkins, Richard J.; Kvarnheden, Anders (Plant pathology, 2021)
Non‐crop plants such as grasses and volunteer plants are an inseparable part of the flora of crop fields and can influence virus incidence in crop plants. The presence of grasses as virus reservoirs can lead to a higher probability of virus incidence in crop plants. However, the role of reservoirs as an inoculum source in agricultural fields has not been well studied for many viral diseases of crops. Grasses have been found to constitute potential reservoirs for cereal‐infecting viruses in different parts of the world. This study revealed that cereal‐infecting viruses such as wheat dwarf virus (WDV), barley yellow dwarf viruses (BYDVs), and cereal yellow dwarf virus‐RPV (CYDV‐RPV) can be found among ryegrass growing in or around winter wheat fields. Phylogenetic analysis showed that a WDV isolate from ryegrass was a typical WDV‐E isolate that infects wheat. Similarly, a ryegrass isolate of barley yellow dwarf virus‐PAV (BYDV‐PAV) grouped in a clade together with other BYDV‐PAV isolates. Inoculation experiments under greenhouse conditions confirmed that annual ryegrass of various genotypes can be infected with WDV to a very low titre. Moreover, leafhoppers were able to acquire WDV from infected ryegrass plants, despite the low titre, and transmit the virus to wheat, resulting in symptoms. Information from the grass reservoir may contribute to improving strategies for controlling plant virus outbreaks in the field. Knowledge of the likely levels of virus in potential reservoir plants can be used to inform decisions on insect vector control strategies and may help to prevent virus disease outbreaks in the future. In the field, ryegrass was found to host cereal‐infecting viruses and its potential role as a reservoir for wheat dwarf virus was confirmed by transmission experiments using leafhoppers.